INTRAMOLECULAR REARRANGEMENT IN THE INFRARED MULTIPLE-PHOTON DISSOCIATION OF DICHLORODIFLUOROETHYLENE - Hancock, G; Mckendrick, K (1988)
The infrared multiple-photon dissociation (IRMPD) of 1,1-dichloro-2,2-difluoroethylene, CF2=CCl2, has been investigated. Under essentially collisionless photolysis conditions, four electronic ground-state radical fragments, CF2(X̃1A1), CCl2(X̃1A1), CFCl(X̃1A′), and CCl(X2II), were detected directly by laser-induced fluorescence (LIF). Production of atomic Cl was also inferred by an indirect infrared chemiluminescence technique. The ratio of products CF2:CFCl:Cl was established within limiting assumptions, by subsidiary experiments involving IRMPD of CF2=CFCl and CF2Cl2. Yields of the various fragments were measured as a function of the photolysis laser energy, allowing conclusions to be drawn on the involvement of alternative modes of decomposition and the extent of possible sequential fragmentation. Arguments are presented for the likelihood of atom migration in the excited parent molecule, prior to bond fission, involving both Cl and F atom shifts. The production of CCl is thought to be most probably the result of secondary photodissociation of the halovinyl radical formed by primary Cl atom loss. © 1988 American Chemical Society.